2020
DOI: 10.1111/joim.13196
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and lifestyle behaviours in relation to longevity: a Mendelian randomization study

Abstract: Background The American Heart Association introduced the Life's Simple 7 initiative to improve cardiovascular health by modifying cardiovascular risk factors and lifestyle behaviours. It is unclear whether these risk factors are causally associated with longevity. Objectives This study aimed to investigate causal associations of Life's Simple 7 modifiable risk factors, as well as sleep and education, with longevity using the two‐sample Mendelian randomization design. Methods Instrumental variables for the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 48 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…Mendelian randomization (MR) is an alternative epidemiological approach that can use genetic variations as instrumental variables (IVs) to uncover the causal relationship between exposure and disease outcomes, and avoiding potential confounders in observational studies ( 15 ). MR has been previously used to explore the association of several risk factors and CVDs, such as smoking ( 16 ), body mass index (BMI) ( 17 ), and alcohol consumption ( 18 ). In this study, a two-sample MR study was performed to examine the potential causal association between physical activity and risk of CVDs using genetic variations associated with self-reported and objective accelerometer-based physical activity identified from published genome-wide association studies (GWASs).…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization (MR) is an alternative epidemiological approach that can use genetic variations as instrumental variables (IVs) to uncover the causal relationship between exposure and disease outcomes, and avoiding potential confounders in observational studies ( 15 ). MR has been previously used to explore the association of several risk factors and CVDs, such as smoking ( 16 ), body mass index (BMI) ( 17 ), and alcohol consumption ( 18 ). In this study, a two-sample MR study was performed to examine the potential causal association between physical activity and risk of CVDs using genetic variations associated with self-reported and objective accelerometer-based physical activity identified from published genome-wide association studies (GWASs).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of established causality between physical activity and CVD is further shown by mendelian randomization (MR) studies that have not been able to establish an association between genetically predicted accelerometer‐measured physical activity and the risk of heart failure, coronary heart disease, myocardial infarction, and stroke [81, 82]. Another MR study found that whereas genetic predisposition to a variety of metabolic risk factors and smoking were associated with lower odds of longevity, there was no such association for genetically predicted self‐reported physical activity [83]. Furthermore, although one twin study has found a single estimate of self‐reported physical activity to be associated with reduced risk of all‐cause and cardiovascular mortality in monozygotic twin pairs with discordant levels of physical activity [84], several other twin studies have shown other results.…”
Section: Introductionmentioning
confidence: 99%
“…After full-text screening, 23 studies were included in the current systematic review . Citation tracking resulted in one additional publication [53]. The 24 included studies were published between 2008 and 2020.…”
Section: Resultsmentioning
confidence: 99%